2019
DOI: 10.1159/000493854
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Patients with Obscure Gastrointestinal Bleeding: A Retrospective Cohort Study

Abstract: Aims: We evaluated the long-term prognosis of patients with obscure gastrointestinal bleeding (OGIB) who underwent capsule endoscopy (CE). Methods: In our hospital, 429 patients underwent CE between November 2007 and March 2012. Among them, 259 patients underwent CE as the first examination for OGIB and were then followed at 77 clinics and hospitals. The clinical characteristics were investigated, including age, gender, overt/occult bleeding, the use of antithrombotic drugs and NSAIDs, complications (liver cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The rate of patients with occult OGIB was reported as 20.4%–41.4%. 19 , 20 , 21 , 22 This study's rate of occult bleeding was approximately 60%, higher than that in previous reports. We reported that the detection rate of the bleeding source for patients with occult OGIB was 27%.…”
Section: Discussioncontrasting
confidence: 61%
“…The rate of patients with occult OGIB was reported as 20.4%–41.4%. 19 , 20 , 21 , 22 This study's rate of occult bleeding was approximately 60%, higher than that in previous reports. We reported that the detection rate of the bleeding source for patients with occult OGIB was 27%.…”
Section: Discussioncontrasting
confidence: 61%
“…This is comparable to the 5-year mortality rate seen when SB adenocarcinoma (all SEER stages combined) is diagnosed (68 %) and worse than when the cancer is localised (85 % survival at 5 years) [7]. A similar study looking at all causes of occult SB bleeding had a 74.7 % 5-year survival rate compared to 89.3 % age matched cohort survival in Japan [8]. This would suggest that a diagnosis of SB angioectasia is both significant and associated with worse outcomes than serious alternative pathologies seen.…”
Section: Discussionmentioning
confidence: 55%
“…The MGIB is a topic of great interest in the gastroenterology practice, being a vastly studied matter, concerning areas such as diagnostic approach, prognosis, treatment and surveillance 1,23,24 . Several factors have been established as potentially influencing the rate of rebleeding 25 ; however, we lack specific knowledge on how to optimize the interpretation of these risk factors to establish the optimal surveillance of MGIB patients.…”
Section: Discussionmentioning
confidence: 99%